Domical ceiling in the Mandapa of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the domical ceiling in the mandapa (pillared hall) of the Suhaveshwar Temple. It is composed of concentric circles made up of small cusps. Each inner circle is offset a little from the outer circle. The centre of the ceiling has a suspended lotus medallion. The ceiling rests on eight pillars. Just above the pillar capitals, the circular portion of the ceiling has small square brackets with sculptures.